Optimal design of stator slot with semi-closed type to maximize magnetic flux connection and reduce iron leakage in high-speed spindle drives - Purwanto, Wawan; Mulani, Firoj; krismadinata, Krismadinata; Maksum, Hasan; Arif, Ahmad; Putra, Dwi Sudarno; Padrigalan, Kathleen Ebora (Universitas Muhammadiyah Magelang, 2024)
A novel approach was devised to optimize the stator slot semi-closed type in order improve the magnetic flux connection and minimize iron leakage in high-speed spindle drives. The concept was executed through a combination of response surface approach including the technique of finite element analysis. The primary objective of this investigation would be to provide an engineering approach which improves the functionality of stator criteria, including the stator slot geometry, coil turn per slot, and wire size. The purpose is to achieve higher flux connection and minimize iron leakage. This study presents an enhanced analytical approach that incorporates the analysis of stator flux connection, finite element calculation of flux connection, and iron leakage analysis of stator variables. The results are analyzed through the utilization of finite element computation, and their accuracy is verified through experimental measurements. The findings suggest the ideal design yields increased magnetic flux connection and reduced iron leakage in comparison to the industrial layout. The precision provided by the suggested model is confirmed through the comparison of the simulation and experimental information. In general, the percentage of errors is estimated to be around 7%.